2019
DOI: 10.1007/s11135-019-00853-1
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of impact of research collaboration on academic performance in Italy

Abstract: The aim of this paper is to investigate theoretically and empirically the impact of research collaborations on the scientific performance of Italian academic institutions. Data are derived from the international Scopus and Web of Science databases. We consider both quantity (the number of publications made in collaboration) and quality indicators from different databases (using indexes such as IF5Y (5-year impact factor of the journal, Web of Science), SJR (SCImago Journal Rank-key integral indicator of the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 127 publications
1
18
0
Order By: Relevance
“…International research collaboration is known to increase research productivity and impact [ 90 92 ]. It is expected that the global situation of AMR is worsened by limited international research collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…International research collaboration is known to increase research productivity and impact [ 90 92 ]. It is expected that the global situation of AMR is worsened by limited international research collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…The Web of Science international citation database uses the impact factor indicator, the Scopus counterpart of which is CiteScore 2 . The literature has confirmed that findings from international collaborations are associated with higher quality than those from national ones are [41][42][43].…”
Section: Literature Reviewmentioning
confidence: 74%
“…The Web of Science international citation database uses the impact factor indicator, the Scopus counterpart of which is CiteScore 2 . The literature has confirmed that findings from international collaborations are associated with higher quality than those from national ones are [41][42][43].…”
Section: Literature Reviewmentioning
confidence: 74%
“…On the other hand, the tax legis lation, which emerged in 1993-1994 in the context of national crisis and with reference to prioritising national interests, has not changed. As a result, Estonian local authorities' current expenditures comprise 22-24% of public expenditures, with the role of local taxes falling below 1% and the main source of local budget revenues being categorical and general grants [43].…”
Section: Main Stages Of Intergovernmental Relations Development In Esmentioning
confidence: 99%